Czy Ewagriusz z Pontu został rzeczywiście potępiony? - Misiarczyk, Leszek (Vox Patrum, 2016)
The article in the first part tries to prove on the basis of the arguments raised in recent studies, especially of A. Casiday, that there are no serious reasons to consider the syriac version S 2 of Kephalaia Gnostica as authentic and the version S 1 as expurged from Origenism. It seems quite the contrary, the version S 1 would be authentic and S 2 would has been contaminated by Origenism of sixth century. So Evagrius would not be the central figure in the so-called first Origenist controversy in the fifth century. In the second part author shows that the name of Evagrius does not appear in the Second Council of Constantinople in 553, in Epistula Synodum de Origene and in Edictum contra Origenem of Justinian. He was condemned probably only by some endemic synod before the official opening of the Council in 553. The question regarding the real validity of this condemnation still remains open. The III Council of Constantinople in 680-681, II Nicean in 787 and patristic authors simply repeat the condemnation of the previus endemic synod without examining the case.